Dark-field X-ray imaging of unsaturated water transport in porous materials - Yang, F.; Prade, F.; Griffa, Michele; Jerjen, Iwan; Di Bella, C.; Herzen, Julia; Sarapata, A.; Pfeiffer, F.; Lura, Pietro (Applied Physics Letters, 2014)
We introduce in this Letter an approach to X-ray imaging of unsaturated water transport in porous materials based upon the intrinsic X-ray scattering produced by the material microstructural heterogeneity at a length scale below the imaging system spatial resolution. The basic principle for image contrast creation consists in a reduction of such scattering by permeation of the porosity by water. The implementation of the approach is based upon X-ray dark-field imaging via Talbot-Lau interferometry. The proof-of-concept is provided by performing laboratory-scale dark-field X-ray radiography of mortar samples during a water capillary uptake experiment. The results suggest that the proposed approach to visualizing unsaturated water transport in porous materials is complementary to neutron and magnetic resonance imaging and alternative to standard X-ray imaging, the latter requiring the use of contrast agents because based upon X-ray attenuation only.
CRIS-Team Scopus Importer:2023-03-08